HUBUNGAN CANCEL CULTURE DENGAN KEPUTUSAN PEMBELIAN SKINCARE PADA GENERASI Z - Nurdiana, Fitri; Warastri, Annisa (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
Purchasing decisions are a process of fulfilling needs through search, evaluation, and post-purchase. One factor that can influence purchasing decisions is cancel culture. The purpose of this study is to determine the relationship between cancel culture and skincare purchasing decisions in Yogyakarta. This study used a quantitative approach with 132 respondents obtained through questionnaires. This study used the Spearman Rho correlation test. The results of this study indicate that cancel culture has a 32.6% influence on purchasing decisions among Generation Z in Yogyakarta, which means that the higher the level of cancel culture, the higher the level of purchasing decisions